Two Sides of Workplace Interactions: How Appreciation and Social Stressors Shape the Relationship Between Job Insecurity and Well-Being - Mauricio E. Garrido Vásquez; Patricia Garrido-Vásquez; Kathleen Otto (Europe's Journal of Psychology, 2020)
Job insecurity has frequently been shown to have a dysfunctional impact on well-being. Based on the conservation of resources (COR) theory, the aim of this study was to investigate how the experience of appreciation at the workplace and the occurrence of social stressors shape the relationship between job insecurity and three indicators of well-being: (a) job satisfaction, (b) (emotional) irritation, and (c) engagement (dedication to the job). In an online study with 117 psychologists, we found that appreciation buffered the relationship between job insecurity and irritation. Social stressors further qualified the moderating effect of appreciation on job satisfaction and dedication, but not fully in the proposed direction. Theoretical implications about the role of more or less social contacts at work (reflected in the experience of appreciation as well as social stressors) when dealing with job insecurity will be discussed.